Acute asthma exacerbations in childhood: risk factors, prevention and treatment - Guibas, G. V.; Makris, M.; Papadopoulos, N. G. (Expert Rev Respir Med, 2012)
Asthma is a heterogeneous disease more appropriately seen as a syndrome rather than a single pathologic entity. Although it can remain quiescent for extended time periods, the inflammatory and remodeling processes affect the bronchial milieu and predispose to acute and occasionally severe clinical manifestations. The complexity underlying these episodes is enhanced during childhood, an era of ongoing alterations and maturation of key biological systems. In this review, the authors focus on such sudden-onset events, emphasizing on their diversity on the basis of the numerous asthma phenotypes.
Keywords: Air Pollutants Allergens Anti-Asthmatic Agents Asthma Child Cholinergic Antagonists Common Cold Humans Hygiene Hypothesis Obesity Phenotype Respiratory Syncytial Virus Infections Rhinovirus Risk Factors Tobacco Smoke Pollution